Granularity of personal intelligence in social networks - Ismail S.; Ahmad M.S.; Hassan Z. (Springer Verlag, 2023)
This chapter introduces and exposes the latest development of agent-modeling framework that emerges from understanding the human behaviour of personal knowledge management (PKM) in social networks. The growing interest in personal knowledge management in exposing personal intelligence has brought out the postulation of GUSC model, which becomes the basis of agent-mediated PKM. In micro view, this GUSC model is the significant tool in understanding the granularity of personal intelligence in social networks. It eventually leads to a theoretical treatment on the bottom-up manifestation of organisational knowledge management from individual PKM processes. © 2014 Springer International Publishing Switzerland.